Comparative Analysis of Antioxidant Enzyme Activities under Hydrogen Peroxide Induced Oxidative Stress in Clinical Isolates of Pathogenic Bacteria - Mahmood, Irfan Wasmi; Farhan, Faten Othman; Ajil, Abdullah Mahmoud (American Journal of Biology and Natural Sciences, 2026)
The analysis showed that the clinical bacterial isolates Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus have different abilities in terms of oxidative stress resistance, which is their different physiological approaches in the infection settings. The results of isolation showed that in respiratory samples P. aeruginosa was dominant (70%), whereas in wound samples E. coli prevailed (48%), which suggests an excellent correlation between the type of samples and efficiency of oxidative defense mechanisms in each of the species. Enzymatic studies indicated that the SOD activities increased significantly with the increment of the concentration of H2O2, peaking at 12.1 U/ mg (+137%), and then fell at concentrations above 50 mM, which indicated that P. aeruginosa was less tolerant to severe oxidative conditions. The linear increase in the CAT activity was up to 25 mM, with a maximum of 41.8 U/mg recorded in P. aeruginosa ( +130) and a slight decrease at 50 mM as a result of enzyme depletion. The POD activity increased by 42-51% according to the isolates with the highest value of 92 nmol/min/mg by P. aeruginosa highlighting its superiority in the detoxification of the peroxides. Concurrently, the total protein concentration steadily declined as the concentration of H2 O2 increased and E. coli exhibited the most significant decline (-38%) and P. aeruginosa the lowest decline (-26%) indicating the degree of protein damage caused by oxidation. Collectively, these results suggest that P. aeruginosa has a more efficient and integrated antioxidant defense system, which is one of the reasons for its persistence and resistance. The overall aim of this study is to assess the enzymatic and protein response of the bacterial isolates under oxidative stress condition in order to understand their adaptive response to oxidative stress for the development of targeted therapeutic scheme against resistant pathogens.